Yahoo Clever wird am 4. Mai 2021 (Eastern Time, Zeitzone US-Ostküste) eingestellt. Ab dem 20. April 2021 (Eastern Time) ist die Website von Yahoo Clever nur noch im reinen Lesemodus verfügbar. Andere Yahoo Produkte oder Dienste oder Ihr Yahoo Account sind von diesen Änderungen nicht betroffen. Auf dieser Hilfeseite finden Sie weitere Informationen zur Einstellung von Yahoo Clever und dazu, wie Sie Ihre Daten herunterladen.
I need help with a proof please?
SecX - 1 / TanX = TanX / 1 + SecX
Been working on this for about an hour and can't get a resolution. Any thoughts?
(secX -1)/tanx = tanx/ (1+secX)
I appreciate the cross multiplication solution but we've been told we can only work on one side of the equation. I saw that one when I started but I was afraid that it would not be accepted.
4 Antworten
- nyc_kidLv 7vor 9 JahrenBeste Antwort
I assume you meant: (SecX - 1) / TanX = TanX / (1 + SecX). If so, proceed:to prove that:
(SecX - 1)(1 + SecX) = (TanX )^2
But (SecX - 1)1 + SecX) = (SecX)^2 - 1 = (1/CosX)^2 - 1 = (1-(CosX)^2)/(CosX)^2 = (SinX)^2/(CosX)^2) = (TanX)^2
!
- vor 9 Jahren
Could you use parenthesis, to better help understand which part is in the numerator and denominator.
Your questions could be:
(secx - 1) / tanx = tanx / (1 + secx)
or
secx - (1 / tanx) = (tanx / 1) + secx
Thanks!
Quelle(n): College Professor - ?Lv 4vor 9 Jahren
You have...
sec=1/cos
tan=sin/cos
1/tan=cos/sin
So, I'd multiply the equation by cosX to get it to...
1 - cos^2(X)/sinX = sinX + 1
Multiplying by sinX gives...
sinX - cos^2(X) = sin^2(X) + sinX
Which boils down to...
0 = sin^2(X) + cos^2(X) = 1 and the universe implodes.